Effect of Farming System (Organic vs. Conventional) and Season on Composition and Fatty Acid Profile of Bovine, Caprine and Ovine Milk and Retail Halloumi Cheese Produced in Cyprus - Tzamaloukas, Ouranios; Neofytou, Marina C.; Simitzis, Panagiotis E.; Miltiadou, Despoina (Foods, 2021)
The present work aimed to evaluate the effect of farming practices and season on the fat and protein content and fatty acid (FA) profile of milk and Halloumi cheese produced in Cyprus. Over a year, raw bulk-tank milk samples from cow, goat, and sheep farms were collected seasonally from all organic (11) and representative conventional (44) dairy farms, whereas Fresh Halloumi cheese samples were collected monthly from retail outlets (48 organic and 48 conventional samples in total). The different farming practices did not affect the milk fat content of ruminants, while protein levels were decreased in organic bovine and caprine milk. Under organic farming practices, milk and cheese contained increased values of total mono-unsaturated FA (MUFA) and poly-unsaturated FA (PUFA), and specific FA, such as oleic, conjugated linoleic, linoleic, and α-linolenic acids. Total saturated FA (SFA) levels were particularly decreased in organic samples and, consequently, the atherogenic indices of milk and cheese were decreased. Season influenced milk and Halloumi cheese FA profile; spring samples had lower SFA and higher PUFA and MUFA concentrations. Overall, the organic farm practices improved the lipid profile of milk and Halloumi cheese, which is more likely attributed to the different feeding strategies applied in organic dairy farms.